PLACEMENT TEST THROUGH WEBSITE ON ENGLISH LANGUAGE SKILL IN POLIMEDIA - Hawa Asma Ul Husna; Anggun Gunawan; Tabitha Kezia (INFOKUM, 2022)
English as an international language is very much needed in the world of work. In Politeknik Negeri Media Kreatif, graduates are expected to be able to communicate proficiently using English so that they can compete in the industrial world globally both at home and abroad considering that the creative industry is growing rapidly. In order for students to be able to use English well in Creative Industry, it is necessary to hold a placement test at the beginning of the study. The purpose of this research is to see the effectiveness of doing a placement test using the website on semester one or two students of the Politeknik Negeri Media Kreatif (Polimedia). This study is a qualitative descriptive research. The subjects of this study were students in semester one or two of the advertising and broadcasting study program. Data collection technique in this study is done by do the placement tests, questionnaires, observations, interviews and literature review. The result of this study is although placement test through website has shortcomings, it is still worth doing in Polimedia